2021
DOI: 10.1016/j.vhri.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Valuation: A Pilot Study for Eliciting Willingness to Pay for a Reduction in Mortality From Vaccine-Preventable Illnesses for Children and Adults in Bangladesh

Abstract: Objectives The contingent valuation (CV) method elicits willingness to pay (WTP) for calculating the value of statistical life (VSL). CV approaches for assessing VSL are uncommon in many low and middle-income countries (LMICs). Between 2008 and 2018 only 44 articles utilized WTP in a health-related field and of these only 5 (11%) utilized CV to assess the WTP for a mortality risk reduction. We elicit WTP estimates and compute VSL using the CV method in Bangladesh. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(68 reference statements)
0
6
1
Order By: Relevance
“…Despite these differences, the WTP-based VSLY value of 4.5 estimated by Patenaude and coauthors falls into the range identified in the current study [ 7 ]. Recent WTP estimates from Bangladesh using a titration method instead of price lists show GDP multiples of about 7, thus even somewhat larger than the values found in the current study [ 9 ]. Note also that, while our research was conducted pre-COVID-19, we observe that in our regression models, wealth had only modest or no statistically significant influence on elicited VSLY.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Despite these differences, the WTP-based VSLY value of 4.5 estimated by Patenaude and coauthors falls into the range identified in the current study [ 7 ]. Recent WTP estimates from Bangladesh using a titration method instead of price lists show GDP multiples of about 7, thus even somewhat larger than the values found in the current study [ 9 ]. Note also that, while our research was conducted pre-COVID-19, we observe that in our regression models, wealth had only modest or no statistically significant influence on elicited VSLY.…”
Section: Discussioncontrasting
confidence: 75%
“…Unfortunately, very few such measurements in low-income countries exist [ 9 ] (see also Robinson and coauthors [ 2 ], for a recent survey). In settings of extreme poverty, illiteracy and cultural context often complicate the elicitation of valuations, and this is especially true in the context of complicated life risks [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary pathway for the increases in cases and deaths averted from an oral vaccine is through alignment in vaccine delivery modality with patient preferences, thereby increasing vaccination uptake among the currently unvaccinated. The likelihood of this phenomena is backed in the literature as well as market studies, indicating that oral delivery mechanisms are strongly favored over injectables, particularly among the unvaccinated or vaccine hesitant [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…One method for increasing the uptake of vaccination in the U.S. is to offer delivery modalities that conform to patient preferences more so than injectable multi-dose vaccines [11]. Several studies have shown that in the U.S., oral vaccines are considered more desirable by patients and a recent study estimated that an oral vaccine against COVID-19 may increase vaccination rates among the unvaccinated by 32%, a population accounting for 92% of the 5,938,358 hospitalization days, 93% of the 817,829 ICU days, and 93% of the 355,276 mechanical ventilation days observed over the December 2021-February 2022 outbreak [11][12][13][14]. One such oral vaccine delivery platform is the Vector-Adjuvant-Antigen Standardized Technology (VAAST) platform, developed by Vaxart, Inc. [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that most of the hypothesis tests associated with S9 passed, indicating people’s preference for a COVID-19 vaccine with high effectiveness and a long duration of protection. In previous CV method studies of scope issues in terms of vaccines, researchers mostly chose one difference in the level of one attribute as a change in scope, such as the category I hypothesis in this paper, e.g., changing the degree of risk of death reduced after vaccination [ 34 36 ], changing the duration of vaccine protection [ 35 , 37 ] or changing the description of disease symptoms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%